2011
DOI: 10.1590/s1806-83242011000600003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different surface treatments and accelerated artificial aging on the bond strength of composite resin repairs

Abstract: Effects of different surface treatments and accelerated artificial aging on the bond strength of composite resin repairs Abstract: The purpose of the present study was to assess the bond strength of composite resin repairs subjected to different surface treatments and accelerated artificial aging. 192 cylindrical samples (CSs) were prepared and divided into 24 groups (n = 8). Half of the CSs were stored in water for 24 h, and the other half were subjected to C-UV accelerated aging for non-metallic specimens. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…The effect of sandblasting may be attributed to an increase in the micromechanical retention that elevates the capability of the added bis-acryl resin to interlock mechanically onto the old resin. These results are in close agreement with many investigations reporting improved bond strengths when the filling composite resin was sandblasted before repair [5,7,9,11]. The findings of the current study demonstrate the importance of sandblasting and micromechanical retention in the bis-acryl temporary resin repair.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The effect of sandblasting may be attributed to an increase in the micromechanical retention that elevates the capability of the added bis-acryl resin to interlock mechanically onto the old resin. These results are in close agreement with many investigations reporting improved bond strengths when the filling composite resin was sandblasted before repair [5,7,9,11]. The findings of the current study demonstrate the importance of sandblasting and micromechanical retention in the bis-acryl temporary resin repair.…”
Section: Discussionsupporting
confidence: 92%
“…Many methods have been introduced for modification of a filling composite resin surface: sandblasting, roughening with diamond instrument, abrasive papers, and acid etching [5][6][7]. Several studies have demonstrated that the application of chemical agent, such as bonding agent or silane coupling agent, enhances the bond strength [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Several surface pretreatment protocols have been evaluated to improve the bond strength of repairing composite resin to old one after acid-etching and silane application 13-16. The results of these previous studies indicate that composite pretreatments might improve the repair bond strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of acid does not require an additional device in the dental practice, such as chair-side air abrasion equipment 18 , surface treatment with 37% phosphoric acid and an adhesive should not be used alone in aged resin 16 . This type of etching did not significantly change the morphological pattern of an aged resin and its action is limited to a superficial cleaning effect 9 , but it can activate the reactivity between a silica surface and silane 14 .…”
Section: Discussionmentioning
confidence: 99%
“…This type of etching did not significantly change the morphological pattern of an aged resin and its action is limited to a superficial cleaning effect 9 , but it can activate the reactivity between a silica surface and silane 14 . Mechanical treatments such as grinding with diamond bur or abrasion are needed 16 before using an acid. In agreement with our results, there was no difference between the control group and etching with phosphoric acid surface treatment 2 .…”
Section: Discussionmentioning
confidence: 99%